Failure as a Learning Asset: Entrepreneurial Cognition, Adaptive Sensemaking, and Innovation Outcomes After Business Failure - Hale Y?lmaz; Tolga Koc; Aylin Erdo?an (Journal of Loomingulisus ja Innovatsioon, 2026)
Business failure is an inherent aspect of entrepreneurial activity, yet it is increasingly recognized as a potential source of experiential learning and strategic renewal rather than merely an indicator of poor performance. Existing studies have primarily emphasized psychological recovery or entrepreneurial resilience, providing limited understanding of how entrepreneurial cognition and adaptive sensemaking transform failure into subsequent innovation outcomes. This study aimed to examine the relationships among entrepreneurial cognition, adaptive sensemaking, organizational learning, opportunity recognition, entrepreneurial resilience, and post-failure innovation performance. A mixed-methods sequential explanatory research design was employed involving 620 entrepreneurs who had experienced at least one business failure and subsequently re-engaged in entrepreneurial activities across multiple industrial sectors. Quantitative data were collected using validated measures of entrepreneurial cognition, adaptive sensemaking, organizational learning, innovation capability, and entrepreneurial resilience and analyzed through Structural Equation Modeling. Qualitative evidence was obtained from semi-structured interviews, entrepreneurial life-history narratives, venture documentation, mentor interviews, and organizational records. Findings revealed that entrepreneurial cognition significantly enhanced innovation capability through adaptive sensemaking and organizational learning, while entrepreneurial resilience strengthened the positive relationship between failure experience and post-failure venture performance. Entrepreneurs who systematically reconstructed meaning from unsuccessful ventures demonstrated stronger opportunity recognition, strategic flexibility, and innovation outcomes. Results suggest that business failure becomes a valuable learning asset when supported by adaptive cognitive processes, continuous organizational learning, and enabling entrepreneurial ecosystems that encourage reflection, experimentation, and strategic renewal.